KINERJA KELOMPOK TANI DALAM MENINGKATKAN PRODUKTIVITAS DI KECAMATAN SURIAN KABUPATEN SUMEDANG - Dadan Nurpalah (LPPM UNSAP, 2026)
Agriculture is a strategic sector that contributes to food security, rural employment, and community welfare. In this context, farmer groups serve as important institutions for strengthening farmers’ capacity, facilitating access to agricultural resources, and supporting improvements in agricultural productivity. This study aimed to analyze the performance of farmer groups in improving agricultural productivity in Surian District, Sumedang Regency, based on five performance dimensions: productivity, service quality, responsiveness, responsibility, and accountability. The study employed a descriptive approach. Data were collected through observation, interviews, and documentation involving farmer-group administrators and members as well as other parties associated with agricultural activities. The data were processed by organizing, classifying, and interpreting the findings according to the five performance dimensions and subsequently analyzed descriptively. The results showed that the overall performance of farmer groups was relatively good. In terms of productivity, the groups contributed to organizing agricultural activities and utilizing available resources, although access to financing, technology, production facilities, and markets remained limited. Service quality was reflected in the provision of information, assistance, and facilitation, but the clarity, fairness, and timeliness of services still required improvement. Responsiveness was demonstrated through participatory planning, although the handling of urgent needs, particularly fertilizer-related complaints, was not fully optimal. Responsibility was reflected in task implementation and members’ commitment, but a clearer division of duties and more regular evaluation were still required. Accountability was demonstrated through compliance with group procedures, although administrative records, financial reporting, and transparency in the distribution of government assistance needed to be strengthened. The study concludes that farmer groups in Surian District have performed reasonably well in supporting agricultural productivity; however, improvements in resource accessibility, service delivery, responsiveness, organizational responsibility, and transparent accountability are necessary to strengthen institutional performance and increase benefits for farmers.